2018
DOI: 10.1002/1873-3468.13082
|View full text |Cite
|
Sign up to set email alerts
|

The role of heparan sulfates in protein aggregation and their potential impact on neurodegeneration

Abstract: Neurodegenerative disorders, such as Alzheimer's, Parkinson's, and prion diseases, are directly linked to the formation and accumulation of protein aggregates in the brain. These aggregates, principally made of proteins or peptides that clamp together after acquisition of β-folded structures, also contain heparan sulfates. Several lines of evidence suggest that heparan sulfates centrally participate in the protein aggregation process. In vitro, they trigger misfolding, oligomerization, and fibrillation of amyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 100 publications
2
51
0
1
Order By: Relevance
“…Tagging modules with GO terms also outlined cell cycle activities (module 6), RNA metabolism (clusters 3 and 5) and Heparan sulfate proteoglycan (HSPGs) biosynthesis (module 8). Interestingly, many of these processes are in agreement with Tau physiological and pathological functions (Hannan et al, 2016;Sotiropoulos et al, 2017;Zhou et al, 2017;Maïza et al, 2018).…”
Section: Network Clustering Highlights Biological Processes Related Tsupporting
confidence: 54%
“…Tagging modules with GO terms also outlined cell cycle activities (module 6), RNA metabolism (clusters 3 and 5) and Heparan sulfate proteoglycan (HSPGs) biosynthesis (module 8). Interestingly, many of these processes are in agreement with Tau physiological and pathological functions (Hannan et al, 2016;Sotiropoulos et al, 2017;Zhou et al, 2017;Maïza et al, 2018).…”
Section: Network Clustering Highlights Biological Processes Related Tsupporting
confidence: 54%
“…A key observation made in this work was that heparin at low concentrations bound to the N-terminal of aSN and induced type-I β-turn structures that are likely a key passageway for entering the fibrillation pathway. Thus, heparan sulfates of the cell surface HSPGs may not only internalize the fibrillar aggregates but also stabilize and/or induce the initial fibrillation-prone states [ 90 ]. If this is indeed so, and this fibrillation triggering also happens in vivo, then the type-I β-turn structures constitute a scaffold for potential targeting by small molecule drugs to be further used therapeutically.…”
Section: Discussionmentioning
confidence: 99%
“…Several papers have shown that the aggregation of α-syn is accelerated by heparin and heparan sulfate (HS; Cohlberg et al, 2002;Ihse et al, 2017;Maiza et al, 2018). HS is a linear polysaccharide expressed on the cell surface or as an extracellular matrix protein (Iozzo, 1998;Medeiros, 2000).…”
Section: α-Synuclein-induced Pathological Changes In Glial Cells Oligmentioning
confidence: 99%
“…Heparan sulfate proteoglycans (HSPGs) are internalized by α-syn in the MO3.13 human oligodendrocyte cell line (Ihse et al, 2017). Furthermore, the presence of HSPGs initiates a conformational change in α-syn forms a native state into an oligomeric state, including β-sheet formation, through protein unfolding (Motamedi-Shad et al, 2009;Maiza et al, 2018). Aggregate α-syn uptake relies on HS by binding to the plasma membrane (Holmes et al, 2013;Ihse et al, 2017).…”
Section: α-Synuclein-induced Pathological Changes In Glial Cells Oligmentioning
confidence: 99%